2007
DOI: 10.1093/cercor/bhm086
|View full text |Cite
|
Sign up to set email alerts
|

Ventrolateral Prefrontal Neuronal Activity Related to Active Controlled Memory Retrieval in Nonhuman Primates

Abstract: It is controversial whether monkeys, like human subjects, can recall, upon instruction, specific information about an event in memory. We therefore tested macaque monkeys on a task that was originally developed to study such active controlled memory retrieval in human subjects and we were able to demonstrate that monkeys, like human subjects, can retrieve, upon command, specific components of previously encoded events. Furthermore, following earlier functional neuroimaging work with human subjects showing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…The present results provide the first cause-and-effect confirmation of the essential role of the VLPFC in active retrieval processing necessary to disambiguate items and their context in memory, which had previously received support from neuroimaging studies on normal human subjects [15,20 -23] and single neuron recording in monkeys [45]. Petrides [15,16] argued that the ventrolateral prefrontal cortical region (areas 45 and 47/12) may be a critical part of the prefrontal cortex for the active controlled retrieval of information in situations in which items of information exist in memory under multiple associations with one another and, therefore, top-down control processing is necessary to disambiguate the memory traces that are assumed to lie in the posterior association neocortex.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The present results provide the first cause-and-effect confirmation of the essential role of the VLPFC in active retrieval processing necessary to disambiguate items and their context in memory, which had previously received support from neuroimaging studies on normal human subjects [15,20 -23] and single neuron recording in monkeys [45]. Petrides [15,16] argued that the ventrolateral prefrontal cortical region (areas 45 and 47/12) may be a critical part of the prefrontal cortex for the active controlled retrieval of information in situations in which items of information exist in memory under multiple associations with one another and, therefore, top-down control processing is necessary to disambiguate the memory traces that are assumed to lie in the posterior association neocortex.…”
Section: Discussionsupporting
confidence: 75%
“…After an instruction to retrieve a specific aspect of a recently memorized complex stimulus (e.g. to retrieve its colour, but not its shape), a class of neurons in the VLPFC responds selectively to the isolation of the instructed aspect of the memorized stimulus (see [45] for details). Thus, there is evidence of neuronal processing isolating particular aspects of memorized experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Recordings in nonhuman primates in the ventrolateral prefrontal cortex have provided evidence at the neuronal level for this active retrieval process. It has been shown that a class of neurons exhibits differential instruction-related activity according to the type of retrieval that must be performed by the monkey, thus signaling the initiation or noninitiation of the retrieval of specific information (44). A second class of neurons increase their firing rate during the delay after the instruction cue and before the test phase and, importantly, their firing is not modulated in the control trials or during the precue interval when the encoded event is simply stored in memory (44).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a class of neurons exhibits differential instruction-related activity according to the type of retrieval that must be performed by the monkey, thus signaling the initiation or noninitiation of the retrieval of specific information (44). A second class of neurons increase their firing rate during the delay after the instruction cue and before the test phase and, importantly, their firing is not modulated in the control trials or during the precue interval when the encoded event is simply stored in memory (44). Thus, the firing of these neurons is not related to encoding, maintenance, or simple recognition of an event in memory but rather to the active retrieval of specific features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation